2012
DOI: 10.7314/apjcp.2012.13.9.4677
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Egg Intake and Prostate Cancer Risk: A Meta-analysis

Abstract: Asian Pacific J Cancer Prev, 13 (9), 4677-4681 IntroductionProstate cancer is the most common cancer among men in United States. It is also one of the leading causes of cancer death among men of all races (Siegel et al., 2012). Although age and family history have been established as strong risk factors for prostate cancer, the role of individual dietary factors is not well understood. The large variation in incidence across countries may also suggest the role of lifestyle and dietary factors in its cause (Yu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…A recent meta-analysis suggested no association with risk of prostate cancer (overall or prostate cancer-specific mortality) [16]. In the HPFS, men who consumed ≥2.5 eggs per week had a 1.8-fold increased risk of developing lethal prostate cancer compared with men who consumed <0.5 eggs per week [17].…”
Section: Dietary Factors: Proteinmentioning
confidence: 99%
“…A recent meta-analysis suggested no association with risk of prostate cancer (overall or prostate cancer-specific mortality) [16]. In the HPFS, men who consumed ≥2.5 eggs per week had a 1.8-fold increased risk of developing lethal prostate cancer compared with men who consumed <0.5 eggs per week [17].…”
Section: Dietary Factors: Proteinmentioning
confidence: 99%
“…It is also one of the leading causes of cancer death among men of all races (XIE and HE, 2013). Literature reviews of PCa epidemiol¬ogy have reported high incidence in Western countries, with lower but typically increasing incidence in less developed countries (Baade et al, 2009;Mohagheghi et al, 2010;Zhang et al, 2011;Center et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several meta-analyses of observational studies have assessed the potential harm of egg intake on such cancers and found a positive association with the risk of breast ( 18 ) and ovarian ( 19 ) cancers, suggested some association with an increased risk of endometrial ( 20 ) and fatal prostate ( 21 ) cancers, but found no association with the risk of total prostate cancer ( 21 ) . However, given that the distribution of egg intake differs across studies, previous meta-analyses ( 19 21 ) that pooled RR comparing the highest with the lowest category of egg intake have limited interpretability in terms of the dose–response relationship.…”
mentioning
confidence: 99%